GREEN SYNTHESIS OF SILVER NANOPARTICLES USING SEED EXTRACT OF ARGYREIA NERVOSA - REBECCA THOMBRE; FENALI PAREKH; NEETA PATIL (International Journal of Pharma and Bio Sciences, 2014)
A simple method for synthesis of biologically stabilized silver nanoparticles was developed using the seed extract of Argyeria nervosa. The nanoparticles synthesized using A. nervosa were characterized by UV-Vis spectrophotometry, X-Ray Diffraction, SEM- EDS and FTIR. The antibacterial and antifungal activity of silver nanoparticles was assessed against Staphylococcus aureus, Bacillus subtilis, Aspergillus niger, Escherichia coli and Pichia pastoris. The silver nanoparticles synthesized thus demonstrated potent antagonistic activity against bacteria and fungi which possess potential applications in medicine and pharmaceutical fields.